IMMUNOLOGIC PARAMETERS IN CHILDREN WITH TUBERCULOSIS INFECTION OF DIFFERENT ACTIVITY - N. V. Korneva; A. A. Starshinova; Yu. E. Ovchinnikova; E. I. Potapenko; O. A. Yakunova; I. F. Dovgalyuk (Медицинская иммунология, 2014)
Two-hundred-eleven patients 3 to 14 years old (mean age 8.60±0.22 years) were observed and clinically evaluated at the Department of Pediatric Phthisiopulmonology, St.Petersburg Institute of Phthisiopulmonology during 2011-2013. The diagnostic protocol included: clinical data, X-rays diagnostics and immunologic assessment. All the patients were examined by DIASKINTEST® (DST) and QuantiferonTB Gold (QFT-G). They were divided into 2 groups, as based on laboratory data, as follows: group I (n= 63), patients with negative DST and QFT-G results; group II (n = 148), with positive results of specific tests. The study was aimed for intergroup comparisons of immune response markers. Positive results of DST and QFT-G suggested clinical activity of tuberculosis infection and are associated with high scores of tuberculin skin test (TST); increased cytokine levels (TNFα, IL-2, IFNγ), higher percentage of CD3+, CD4+ и CD95+ cells, elevated levels of specific IgG antibodies (anda TB ELISA); high titers of complement fixation test for mycobacteria, and activation of neutrophils. Positive results of DST and QFT-G in the patients are more often associated with active infection.